Treatment of pyloric stenosis due to corrosive gastritis: indications of subtotal gastrectomy (Luis M Bosch del Marco) or resection of the mucosa and sub-mucosa of the anthropyloric and pylorus (P Larghero Ibarz) - Barani, Julio C (Cirugía del Uruguay, 2020)
Presented at session 13th July 1955